STUDENTS’ SATISFACTION WITH THE TESTING METHODS PROVIDED BY MOODLE-BASED LEARNING MANAGEMENT SYSTEM: A SURVEY IN GENERAL ENGLISH 2 CLASSES IN A PRIVATE HIGHER EDUCATION INSTITUTION IN BANDUNG, INDONESIA - Levita Dwinaya (Jurnal Sastra - Studi Ilmiah Sastra, 2021)
The outbreak of the novel corona virus COVID-19 has changed the way people interact to each other as well as the way people do in almost every walk of life, including education. Because of the physical distancing rule to slow down the spread of the virus, education system has now been facing a 3600 change in the way teachers deliver materials, interact to as well as with students and assess students’ progress in their learning process facilitated by educational technology such as Moodle-based learning management system or LMS. This study was conducted to find out students’ satisfaction with the testing methods delivered via a university’s LMS in General English 2 class by employing a five-point-Likert scale questionnaire of which result was analyzed using descriptive statistical formulas. The results indicate that students involved in this study are highly satisfied with the testing methods provided by the university’s LMS, which shows the adequate online teaching and learning management proficiency of the faculty members. This study calls for further research into the exploration of Moodle-based LMS affordance in assessing specific language skills.